Hepatoprotective Effect of Caesalpinia sappan L. Ethanolic Extract on Alloxan Induced Diabetic Rats: Efek Hepatoprotektif Ekstrak Etanol Caesalpinia sappan L pada Tikus Diabetes Terinduksi Aloksan - Holidah, Diana; Dewi, Ika Puspita; Siregar, Iskandar P. A.; Aftiningsih, Dwi (Universitas Tadulako, 2022)
Background: The complications of Diabetes Mellitus (DM) may lead to other health problems such as heart attack, stroke, kidney failure, leg amputation, vision loss, nerve and liver damage. Increasing free radicals in the hyperglycemic condition in DM can induce inflammation and necrosis that lead to liver damage. This damage causes elevated hepatic enzymes such as aspartate aminotransferase (AST) and alanine aminotransferase (ALT). Malondialdehyde (MDA) is a biomarker that is often used to evaluate oxidative stress including in vivo experimental models of diabetes. Caesalpinia sappan L. is one of the well-known herbs which has a strong antioxidant effect and has various pharmacology activities, including antidiabetic and hepatoprotective. Objectives: This study is aimed to investigate the effect of Caesalpinia sappan L. ethanolic extract on liver function and antioxidant status in diabetic rats. Material and Methods: Twenty-four diabetic male rats were divided into six groups consisting of the normal control group, negative control, positive control, and Caesalpinia sappan L. extract treatment group at a dose of 50, 100, and 400 mg/kg BW. The diabetic status was induced by alloxan. The animals were given treatment for 14 days, and on the 15th day, their blood and liver were collected to measure the level of AST, ALT, plasma MDA, and liver MDA. Results: The extracts of Caesalpinia sappan L. can decrease the levels of AST and ALP and show a low number of MDA levels both in plasma and liver on diabetic rats induced by alloxan. The dose of 100 mg/kg BW has the best result for lowering AST and ALT levels; meanwhile, the dose of 400 mg/kg BW shows the least value of MDA among all the doses. Conclusions: The Caesalpinia sappan L. ethanolic extract has potential activity as the hepatoprotective and antioxidant in diabetic status.